O jornalismo como palco de disputas discursivas : o movimento feminista no Jornal A Gazeta do Espírito Santo (1986-2016) - Machado, Viviane Ramos (2018)
This work intends to understand how feminist discourses are constructed in the journalism discursive territory, specially in Jornal A Gazeta, from 1986 to 2016. We started with the assumption that journalism provides visibility to discourses made invisible by cultural standards in it's normality and repetition, and, by doing that, creates the news that guides our everyday life. We dealt, most of all, with the communication, current object in our everyday life, with sensible existence, with domain of what is real and established in practices and objects that we see, hear and feel. For the theoretical and methodological framework, we adopted the Depth Hermeneutics (DH), developed by Thompson (2011), a social investigation practice that allows the understanding of how symbolical actions are made. In addition to, we outlined the most important feminist movement milestones in Espírito Santo, starting with the vestiges left by news reports in the analyzed newspaper, worked out a quantitative analysis of the data obtained with the research and analyzed six texts selected under the Critical Discourse Analysis, proposed by Norman Fairclough (2001). We perceived, well-founded by the empirical research, that there is a diversity in the content published about the feminist movement. Even though, most of it are published in spaces dedicated to fictional and cultural products, we were also able to identify texts with a more deep political content, that oppose to distinct society organization methods, refute laddish and conservative standards, illustrate the constant struggle for equal rights between men and women, as well as especulate the future of feminism. The reproduction of feminist discourses in the newspaper, however, was not limited by positive constructions; we also identified the emergence of texts that reproduce the stereotype of a housewife, hypersexualized, and excluded from positions of power in the society